Design of a Mamdani Fuzzy Logic Prototype System for Free-Range Chicken Egg Incubators - Manullang, Maribeth Adventina; Arihta, Michael; Rahmadewi, Reni (Journal of Energy and Electrical Engineering, 2025)
This research aims to design a temperature and humidity control system for chicken egg incubators using the Mamdani Fuzzy logic method. The main problem addressed is the fluctuation of temperature and humidity in conventional systems that still rely on on/off control. The developed system utilizes DHT sensors as temperature and humidity gauges, Arduino as a microcontroller, and regulates the light intensity of incandescent lamps using an AC dimmer. Mamdani Fuzzy Logic is used to process two inputs, namely temperature and humidity and produce an output in the form of the brightness level of the incandescent lamp. The system relies on nine Fuzzy rules in making decisions based on variations in input conditions. The test results show that the system is able to provide appropriate responses to changes in temperature and humidity, and produce outputs in accordance with the designed rules, such as Rule R1, R5, and R9. Thus, this system succeeds in maintaining the stability of the temperature in the incubator, so as to increase the efficiency and success of the egg hatching process. Overall, the application of Mamdani Fuzzy Logic proved effective in designing an intelligent control system for the incubator.